Dificuldades no diagnóstico laboratorial das hemoglobinopatias - Naoum, Paulo Cesar [UNESP]; Bonini-Domingos, Claudia R. [UNESP] (My University, 2007)
There are various types of hemoglobinopathies that are characterized by variants of abnormal hemoglobins (eg. Hb S, HbC, unstables Hb, etc.) and thalassemias (eg. alpha, beta, beta/delta, etc.). Hemoglobinopathies account for some of the most common single gene disorders worldwide with at least 5% of the world's population having one or more serious genetic abnormalities. Because of the clinical and genetic heterogenity of these disorders, a laboratory investigation is fundamental to establish the diagnosis of the different variants of the abnormal hemoglobinopathies and thalassemias. This article reports on the laboratory diagnostic difficulties caused by molecular complexity of these abnormalities.
Dificulties on the laboratorial diagnosis of hemoglobinopathies
Keywords: Hemoglobinopathies; Sickle cell disease; Thalassemias